Language, Power, and Health Literacy: A Critical Discourse Analysis of Health Communication at Community Health Centers - Muh Kholiq; Sri Ningsih; Tri Budiarta (Journal of Language and Health, 2025)
This study examines the role of language in public health practices at Community Health Centers (Puskesmas) in Depok City by integrating sociolinguistic perspectives, Fairclough’s Critical Discourse Analysis (CDA), and the concept of health literacy. It aims to investigate how linguistic choices, power relations, and levels of health literacy shape the effectiveness of communication between healthcare professionals and patients. Employing a qualitative descriptive approach with a case study design, data were collected through observations of medical interactions, semi interviews with healthcare providers and patients, and document analysis of health communication materials, including posters, brochures, and official social media content. The findings reveal that the dominance of medical registers and institutional discourse structures reflects asymmetrical power relations that may hinder patient comprehension and participation. However, the use of linguistic accommodation strategies and simplified language significantly enhances patients’ health literacy and trust. These findings highlight the importance of a critical linguistic perspective in the development of inclusive and effective public health communication policies.